Policy Networks Analysis in Advocacy of Indonesian Marriage Law Amendment to Raise the Minimum Marriage Age - Fajriannoor Fanani; Teguh Yuwono; Nurul Hasfi; Dewi Erowati (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This study aims to analyze the revision of Indonesia’s Marriage Law in 2019 by applying the policy network approach developed by David Marsh and Martin Smith, with a particular focus on how network dynamics shape policy outcomes for the minimum marriage age of women. The research contributes to the field of public policy and political communication by offering a relational perspective that moves beyond actor-centered explanations and highlights the importance of network structures, interactions, and resource distribution. Using a qualitative case study design, this research examines four analytical dimensions: network environment, network structure, actors’ interests and resources, and patterns of network interaction. Data were collected through document analysis, in-depth interviews with activists involved in the advocacy process, and various secondary data. The findings reveal that the success of the amendment was driven by a cohesive policy network built mainly by civil society coalitions providing advocacy, expertise, and public pressure. However, the study also finds that this success was strongly influenced by a favorable policy window shaped by key political events, including judicial changes and shifting elite alignments, which reduced resistance to reform. These results highlight that while policy networks are crucial in organizing and advancing advocacy efforts, their effectiveness is contingent upon broader political opportunities.